V for vitamin, inverted V for lack of it: A rare case of subacute combined degeneration of cord with bladder symptoms and associated multiple Tarlov cysts - KC, Shashidhar; V, Savitha; Bs, Vathul (Indian Journal of Case Reports, 2022)
Subacute degeneration of cord (SACD) is a rare presentation of a common disease and it should be kept in mind when the patient develops symptoms of peripheral neuropathy. This is a case of a 65-year-old male who presented with pins and needles sensation of bilateral hands and feet and with difficulty in voiding. Neurological examination showed large fiber neuropathy with an exaggerated knee jerk, absent ankle jerk, extensor plantar, and a positive Romberg’s sign. Routine laboratory investigations showed low hemoglobin and low vitamin B12 levels. Magnetic resonance imaging of the spinal cord showed a hyperintense lesion in the posterior aspect of the cervical cord with a classical “inverted V” sign on the axial section which is suggestive of SACD. Coincidentally, there were multiple Tarlov cysts present. Finally, the patient improved with vitamin B12 injections. This case is unique as an association of SACD with Tarlov cysts with a classical inverted V sign has not been reported according to the literature.